Pichia pastoris-expressed dengue 3 envelope-based virus-like particles elicit predominantly domain III-focused high titer neutralizing antibodies - Tripathi, Lav; Mani, Shailendra; Raut, Rajendra; Poddar, Ankur; Tyagi, Poornima; Arora, Upasana; de Silva, Aravinda; Swaminathan, S; Khanna, Navin (Frontiers in Microbiology, 2015)
Dengue poses a serious public health risk to nearly half the global population. It causes ~400 million infections annually and is considered to be one of the fastest spreading vector-borne diseases. Four distinct serotypes of dengue viruses (DENV-1, -2, -3 and -4) cause dengue disease, which may be either mild or extremely severe. Antibody-dependent enhancement (ADE), by pre-existing cross-reactive antibodies, is considered to be the major mechanism underlying severe disease. This mandates that a preventive vaccine must confer simultaneous and durable immunity to each of the four prevalent DENV serotypes. Recently, we used Pichia pastoris, to express recombinant DENV-2 E ectodomain, and found that it assembled into virus-like particles (VLPs), in the absence of prM, implicated in the elicitation of ADE-mediating antibodies. These VLPs elicited predominantly type-specific neutralizing antibodies that conferred significant protection against lethal DENV-2 challenge, in a mouse model. The current work is an extension of this approach to develop prM-lacking DENV-3 E VLPs. Our data reveal that P. pastoris-produced DENV-3 E VLPs not only preserve the antigenic integrity of the major neutralizing epitopes, but also elicit potent DENV-3 virus-neutralizing antibodies. Further, these neutralizing antibodies appear to be exclusively directed towards domain III of the DENV-3 E VLPs. Significantly, they also lack discernible ADE potential towards heterotypic DENVs. Taken together with the high productivity of the P. pastoris expression system, this approach could potentially pave the way towards developing a DENV E-based, inexpensive, safe and efficacious tetravalent sub-unit vaccine, for use in resource-poor dengue endemic countries.